Genetic identification of methicillin resistant Staphylococcus aureus (MRSA) isolated from diabetic foot ulcers and evaluating the inhibition activity of reuterin against this bacteria - Khulood Abdulkareem Hussein,; Abdulmutalib Abdulla Mohammed,; Sundus Baqer Dawood,; Sajjad Salim Issa, (Journal of the Pakistan Medical Association, 2024)
Objective: To genetically diagnose the isolates of methicillin-resistant staphylococcus aureus taken from patients with severe diabetic foot infections, and to test the inhibitory effect of reuterin on the growth of these bacteria. Method: The experimental study was conducted from June to November 2021 at the Diabetes Unit of Al-Faihaa General Hospital, Basrah, Iraq, and comprised foot ulcer swabs from the necrotic lesions of patients with type 2 diabetes. The swabs were cultivated first in brain heart infusion broth media, and then streaked on Mannitol salt agar and staphylococcus chromogeneic agar media for phenotypic and genetic analysis. The genetic identification of bacteria was confirmed by deoxyribonucleic acid extraction, and methicillin-resistant staphylococcus aureus was confirmed by the presence of plasmid mecA gene. The inhibition activity of reuterin towards methicillin-resistant staphylococcus aureus was determined using the minimum inhibitory concentration test. All data was analyzed with SPSS version 23. Results: There were 62 patients 6 (66.7%) males and 5(33.3%) females with a mean age of 46±3 years. Of the total isolates, 9(14.5%) gave mauve to purple colour on staphylococcus chromogeneic agar, which was then genetically confirmed as methicillin-resistant staphylococcus aureus. The minimum inhibitory concentration value of these bacteria was 10µl/ml at 16mm inhibition zone diameter. There was no cytotoxicity of reuterin to human red blood cells. Conclusion: Reuterin was found to be a natural antimicrobial substance suitable for use to disinfect diabetic foot wounds from bacterial contamination and infection, especially those casued by methicillin-resistant staphylococcus aureus. Key Words: Methicillin, Staphylococcus aureus, Agar, Diabetic, hydroxypropionaldehyde, Microbial Sensitivity, Mannitol, DNA, Erythrocytes, Plasmids, Brain